Evidence-based Oncology. - Williams, C. J. (Christopher John Hacon) (Evidence-based medicine., 2008)
A comprehensive text concentrating on optimum treatment for solid tumours in adults, based on available evidence. The most commonly asked questions for treatment of the different conditions will be identified and evidence based strategies suggested. It will be kept up to date with its own website.